Immunodeficiency Promotes Adaptive Alterations of Host Gut Microbiome: An Observational Metagenomic Study in Mice - Zheng, Shuyu; Zhao, Tingting; Yuan, Shuijuan; Yang, Lingyu; Ding, Jinmei; Cui, Li; Xu, Mingqing (Frontiers in Microbiology, 2019)
The crosstalk between gut microbiota and immune state of the host is an essential focus in academia and clinics. To explore the dynamic role of the microbiota in response to immune deficiency, we comprehensively assessed the microbiome of 90 mouse fecal samples, across 3 time points including two immunodeficiency models, namely severe combined immunodeficient (SCID) mice and non-obese diabetic SCID (NOD/SCID) mice, with BALB/c as a control strain. Metagenome analysis revealed a decrease in alpha diversity and a clear structural separation exist in the microbiota of immunodeficient mice. Although nuances exist between SCID and NOD/SCID mice, an increase in the protective microbiota, in particular Lactobacillus, contributed the most to the discrimination of immunodeficient and control mice. Further data regarding the RBC concentration and serum IgA level during different stages of development support the alleviation role of the microbiota in the progress of immune deficiency, which is called microbial compensation. Taken together, these results demonstrated a dynamic impact of immunodeficiency on gut microbiota and the adaptive alteration of microbiota that may influence the host state.